Narzullaev Nozimjon Sobirjonovich - Narzullaev Nozimjon Sobirjonovich (Academia One Publishing, 2026)
This article explores the historical development of the hotel and restaurant industries from ancient times to the modern era, with a particular focus on Uzbekistan’s approach. Hospitality has evolved from the provision of basic needs for food and shelter to a global industry encompassing luxury accommodations, fine dining, and mass-market service chains. Through a chronological approach, the article examines the origins of inns and public dining in ancient civilizations, the rise of modern restaurants during the French Revolution, the growth of hospitality during industrialization, and the diversification of the sector in the 20th and 21st centuries. This study draws upon authentic historical sources to highlight major milestones and transformations within the industry, while also considering Uzbekistan’s unique contributions and methods within this global context.
Keywords: hospitality; hotel industry; restaurant industry; history of hospitality